The crystal structure of 3-amino-2-formyl-1-phenyl-9,10-dihydrophenanthrene-4-carbonitrile, C22H16N2O - Cheng Longdie; Luo Guoyong; Wang Xulan; Ye Jianghai; Lang Tianqiong (Zeitschrift für Kristallographie - New Crystal Structures)
C22H16N2O, monoclinic, P21/c, (no. 14), a = 9.689(7) Å, b = 16.800(10) Å, c = 10.379(7) Å, β = 92.229(17), V = 1,688.22(18) Å3, Z = 4, Rgt(F) = 0.0584, wRref(F2) = 0.1572, T = 273(2) K.